Islamic Law Frameworks for Addressing Marriage Delays during Public Health Crises - Desminar, Desminar; Habibulloh, Habibulloh; Saputra, Romi; Abrar Sulthani, Dinil; Irawan, Andi (KARSA Journal of Social and Islamic Culture, 2024)
This study examines the postponement of marriages at the Office of Religious Affairs (KUA) in Koto Tangah District during the COVID-19 pandemic as an effort to address health and social challenges, focusing on the perspective of Islamic law. The government's social restrictions led many couples to postpone or cancel their weddings, especially during the large-scale social restrictions period. This research aims to understand marriage postponement as a strategy to navigate pandemic challenges from an Islamic law perspective in Koto Tangah District, Padang City, and its impact on couples and society. The method used is field research with a descriptive qualitative approach. The findings show that marriage postponement was effectively carried out through schedule coordination with couples despite pressure from the brides and grooms. Health protocols were the primary reason for the delay, and KUA strictly limited the number of weddings if safety standards were not met. The postponements had significant psychological and economic effects on the couples, while society had mixed responses to the policy. KUA faced challenges in implementing marriage delays, especially regarding facilities and communication with engaged couples